IMPEDANCE SPECTROSCOPY OF POLYCRYSTALLINE TIN DIOXIDE FILMS - D. V. Adamchuck; V. K. Ksenevich; N. I. Gorbachuk; V. I. Shimanskij (Приборы и методы измерений)
The aim of this work is the analysis of the influence of annealing in an inert atmosphere on the electrical properties and structure of non-stoichiometric tin dioxide films by means of impedance spectroscopy method. Non-stoichiometric tin dioxide films were fabricated by two-step oxidation of metallic tin deposited on the polycrystalline Al2O3 substrates by DC magnetron sputtering. In order to modify the structure and stoichiometric composition, the films were subjected to the high temperature annealing in argon atmosphere in temperature range 300–800 °С. AC-conductivity measurements of the films in the frequency range 20 Hz – 2 MHz were carried out. Variation in the frequency dependencies of the real and imaginary parts of the impedance of tin dioxide films was found to occur as a result of high-temperature annealing. Equivalent circuits for describing the properties of films with various structure and stoichiometric composition were proposed. Possibility of conductivity variation of the polycrystalline tin dioxide films as a result of аnnealing in an inert atmosphere was demonstrated by utilizing impedance spectroscopy. Annealing induces the recrystallization of the films, changing in their stoichiometry as well as increase of the sizes of SnO2 crystallites. Variation of electrical conductivity and structure of tin dioxide films as a result of annealing in inert atmosphere was confirmed by X-ray diffraction analysis. Analysis of the impedance diagrams of tin dioxide films was found to be a powerful tool to study their electrical properties.